Stages of employment readiness and propensity to return to work - Wan Abdullah, Wan Arnidawati; Arshat, Zarinah; Hassan, Mohammad Mujaheed; Eng, Ng Eng; Zamani, Nur Liana (ASR Research India, 2022)
The Return to Work (RTW) Program has been in place since 2007 by the Social Security Organisation (SOCSO) Malaysia in response to an increase in the number of commuting accident cases, invalidity claims, the financial instability of social security funds, and the length of time that are disabled. In order to reintegrate injured workers back into society, the programme provides resources for physical and occupational rehabilitation. Thus, assessing their suitability for formal employment is crucial before assisting them in returning to work. This research aimed to see if there was a link between employment readiness and the likelihood of RTW among participants in SOCSO’s Malaysia RTW programme. The study used a descriptive quantitative research design. From January to December 2017, all data for 705 participants recommended for the RTW Program was collected from SOCSO personal electronic files. The Lam Assessment on Stages of Employment Readiness (LASER) was used to measure employment readiness of Action, Contemplation, and Pre-Contemplation stages. Data on sociodemographics, employment readiness stages, and the time it took to return to work were analysed. T-Test and ANOVA were used to assess the difference between demographic characteristics and employment preparedness with the pace to RTW. A total of 407 people were able to return to work, with more than half of them doing so in less than 90 days. More than half of respondents (60%) in the Pre-Contemplation and Action stage and 63% of the contemplation stage participants returned to work. According to the findings, there is no statistically significant difference in group means, which contradicts earlier research. The correlation between readiness and RTW duration was also analysed, but no significant association was discovered. Recognising the RTW scenario in Malaysia, more research is needed to examine the assessment management and other RTW predictive factors. The attitudes and behaviours of RTW were also not adequately explored in this study, which should be addressed in future research.